TEACHING AND LEARNING PERFORMANCE: THE PERCEPTION OF LECTURERS OF ENGLISH AT MEDICAL COLLEGES IN JAMBI - Ningsih, Irna (Kopertis Wilayah X (Sumbar, Riau, Jambi, dan Riau Kepulauan), 2018)
This study was aimed at investigating the perception of the lecturers of English toward their teaching and learning performance by finding out the most dominant indicators of performance in terms of planning and preparing, conducting learning process, and learning evaluation. The design of the study was survey study involved sixteen lecturers of English at ten different medical colleges in Jambi as participants. The data were obtained through a set of questionnaire. The percentage analysis was used as technique to find out the most dominant indicators of teaching and learning performance implemented by lecturers of English at medical colleges in Jambi in terms of the three sections (planning and preparing, conducting learning process, learning evaluation).